2019
DOI: 10.1002/eat.23118
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder symptoms across the weight spectrum in Australian adolescents

Abstract: Objective: Despite known associations between eating disorders and obesity, little is known about the current prevalence of symptoms of eating disorders across the weight spectrum. This study therefore aimed to estimate the population prevalence of eating disorder symptoms in relation to weight status in adolescents.Method: The sample comprised 3,270 participants (14-15 years; 52% boys) drawn from Wave 6 of the Longitudinal Study of Australian Children. Symptoms of anorexia nervosa (AN) and bulimia nervosa (BN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 39 publications
0
31
0
3
Order By: Relevance
“…Findings suggest that youth with ARFID are significantly more likely to develop this disorder at a younger age, experience a longer duration of symptoms, are more likely to be male, have longer inpatient stays for medical stabilization, and present with weights higher than those with AN but lower than those with BN [2,3,4,6,7]. Previous research in the eating disorder literature suggests that clinical and medical presentations differ depending on eating disorder diagnosis, age, weight status, and symptom duration and frequency [6,8,9,10]. Given that ARFID is a recent addition to the DSM-5, research efforts to describe the heterogeneity within ARFID are still underway [2,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Findings suggest that youth with ARFID are significantly more likely to develop this disorder at a younger age, experience a longer duration of symptoms, are more likely to be male, have longer inpatient stays for medical stabilization, and present with weights higher than those with AN but lower than those with BN [2,3,4,6,7]. Previous research in the eating disorder literature suggests that clinical and medical presentations differ depending on eating disorder diagnosis, age, weight status, and symptom duration and frequency [6,8,9,10]. Given that ARFID is a recent addition to the DSM-5, research efforts to describe the heterogeneity within ARFID are still underway [2,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Children and adolescents with high BMI have also demonstrated an increased risk of ED risk factors [ 15 ] and a higher risk of developing EDs compared to those with healthy weight [ 16 ]. Compensatory behavioural symptoms such as vomiting and excessive exercise have been reported to be common among adolescents with high BMI [ 17 ]. Whilst EDs and high BMI have traditionally been conceptualised as separate problems, with independent trajectories and methods of treatment and prevention [ 18 ], recent studies have found that they share multiple psychological and environmental risk factors such as dieting, body dissatisfaction, media exposure, perfectionism, trauma, weight teasing by family and friends and internalisation of the cultural beauty ideal [ 19 , 20 ].…”
Section: Eating Disorders and High Bmi Are Significant Problems Inmentioning
confidence: 99%
“…Die Ergebnisse der geschlechtsspezifischen Analysen indizieren innerhalb der Gruppe behandlungsaufsuchender Jugendlicher mit Übergewicht und Adipositas bei Mädchen im Vergleich zu Jungen eine stark erhöhte Essstörungspsychopathologie und gewichtsbezogene Selbststigmatisierung, während sich beide Geschlechter nicht in allgemeiner Psychopathologie und körperlicher Beschwerdelast unterscheiden. Diese geschlechtsspezifische Vulnerabilität für körper-und essensbezogene Psychopathologie stützt bereits gefundene Zusammenhänge bei Jugendlichen mit Übergewicht zwischen dem weiblichen Geschlecht und einer erhöhten gewichtsbezogenen Selbststigmatisierung [14] sowie einer ausgeprägteren Essstörungspsychopathologie [4,[15][16][17]. Die Ergebnisse bezüglich ausbleibender geschlechtsspezifischer Unterschiede der Lebensqualität widersprechen bisherigen nationalen und internationalen Befunden [4,8,13].…”
Section: Diskussionunclassified
“…5,9 % [1]. Die Bedeutsamkeit einer wirksamen Behandlung von Übergewicht und Adipositas im Jugendalter ergibt sich durch ihre Persistenz [2] sowie eine Vielzahl psychischer und physischer Komorbiditäten [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Als Therapie der Wahl bei Adipositas im Kindes-und Jugendalter gilt ein multimodales Behandlungskonzept mit verhaltens-und familientherapeutischen Aspekten [18], dessen Effekte jedoch insgesamt als niedrig bis moderat einzuschätzen sind [19].…”
Section: Introductionunclassified
See 1 more Smart Citation